Cognitive complaints of adults with attention deficit hyperactivity disorder - Fuermaier, Anselm B. M.; Tucha, Lara; Koerts, Janneke; Aschenbrenner, Steffen; Weisbrod, Matthias; Lange, Klaus W.; Tucha, Oliver (The clinical neuropsychologist, 2014)
Executive dysfunction of adults with ADHD is often associated with poor self-awareness of problems, such as in emotional competence, emotional recognition, and driving competence. However, with regard to cognitive functioning, little is known about how adults with ADHD evaluate their own cognitive performance. A total of 77 adults with ADHD and 116 healthy adults were assessed with self-report scales measuring several aspects of cognition. Significance and effect sizes as well as the proportion of patients perceiving impairments were calculated. Further analysis was carried out on the frequency of patients perceiving various types of impairments. Adults with ADHD perceived themselves to have significant and severe dysfunction in all areas of cognition assessed as a group. Furthermore, the majority of patients reported multiple impairments in attention, memory and executive functioning. The present study demonstrated that adults with ADHD are aware of problems in cognitive functioning as shown by considerable perceived neuropsychological impairment in the majority of patients. Patients with ADHD tended to report cognitive impairments in multiple domains rather than impairments in specific functions.